Uma abordagem orientada a modelos para desenvolvimento de sistemas ERP de varejo na Web utilizando características funcionais de usabilidade - Quintale, Diego Heitzmann (Universidade Federal de São Carlos, 2015)
ERPs are complex systems that handle large amounts of data and links among this data providing to its users different information. Usually, developers of this type of application dedicate their efforts to guarantee correctness of the functionality and information consistency; so usability issues become secondary. It is widely recognized that ERP systems own complex interfaces that negatively affect the ability to use these systems. However, it is observed that certain rules that assist to improve interfaces may be automated, thus it is possible to create automated processes to help the development of such applications. This work presents a model driven approach for retail ERP systems with functional usability features (functional features with high impact on usability), called FUF. This study consisted in two stages. In the first one was made literature and market research of retail ERP systems. The second step was the development of a metamodel for retail ERP systems with functional usability features, called MetaUsaERPWeb, it was also carried out the development of a M2C transformer for MetaUsaERPWeb with PHP target platform. Finally, in the last step, the validation of the proposal was made in a case study, with two tests: the first conducted an experimental study to validate the proposed approach against the traditional approach. The results showed that the groups using MetaUsaERPWeb were more efficient, produce more lines of code and better applications. The second analysis compared the applications developed from the traditional approach and the use of MetaUsaERPWeb (first analysis); the results showed that applications built with MetaUsaERPWeb violated least usability heuristics in 60 % of cases.
A model driven development approach for retail ERP systems on web with functional usability features
Keywords: ERP; Desenvolvimento dirigido a modelos; Heurística de usabilidade; Características funcionais de usabilidade; Model driven development; Usability heuristics; Functional usability features; Sistemas de computação; Interação homem-máquina; Sites da web; Computer systems; Human-computer interation; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO